2018
DOI: 10.1523/jneurosci.2360-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Domain-General and Domain-Specific Patterns of Activity Supporting Metacognition in Human Prefrontal Cortex

Abstract: Metacognition is the capacity to evaluate the success of one's own cognitive processes in various domains; for example, memory and perception. It remains controversial whether metacognition relies on a domain-general resource that is applied to different tasks or if self-evaluative processes are domain specific. Here, we investigated this issue directly by examining the neural substrates engaged when metacognitive judgments were made by human participants of both sexes during perceptual and memory tasks matche… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

35
284
3
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 258 publications
(326 citation statements)
references
References 74 publications
(134 reference statements)
35
284
3
4
Order By: Relevance
“…The newly involving fMRI activities during the redecision phase in comparison to those during the first decision-making phase are not necessarily related to metacognition, could be generally associated with the second decision-making. However, the fMRI activities in the MCN predominately occurring during the redecision phase were subject to the decision uncertainty levels on the preceding decisions, similar to the findings in the previous studies (Fleming et al, 2012;Morales et al, 2018;Qiu et al, 2018;Wan et al, 2016). Specifically, we here found that metacognitive abilities of decision uncertainty monitoring were lower, and the strengths of fMRI activities in the MCN, especially in dACC, were consistently much more reduced in SZ than HC.…”
Section: Hypo-activity In the Mcn And The Metacognitive Deficitsupporting
confidence: 89%
See 2 more Smart Citations
“…The newly involving fMRI activities during the redecision phase in comparison to those during the first decision-making phase are not necessarily related to metacognition, could be generally associated with the second decision-making. However, the fMRI activities in the MCN predominately occurring during the redecision phase were subject to the decision uncertainty levels on the preceding decisions, similar to the findings in the previous studies (Fleming et al, 2012;Morales et al, 2018;Qiu et al, 2018;Wan et al, 2016). Specifically, we here found that metacognitive abilities of decision uncertainty monitoring were lower, and the strengths of fMRI activities in the MCN, especially in dACC, were consistently much more reduced in SZ than HC.…”
Section: Hypo-activity In the Mcn And The Metacognitive Deficitsupporting
confidence: 89%
“…Although there have existed many clinical studies on the metacognitive deficits in SZ, a lack of operational definition of metacognitive deficits makes it difficult to use a proper experimental paradigm to investigate the underlying neural mechanisms. To date, there are growing interests in neuroscience to investigate neural mechanisms of metacognition (Fleming, Huijgen, & Dolan, 2012;Kiani & Shadlen, 2009;Miyamoto et al, 2017;Morales, Lau, & Fleming, 2018). Nevertheless, the neural accounts linking the metacognitive deficits and clinical symptoms in SZ remain largely obscure (Buchy, Stowkowy, MacMaster, Nyman, & Addington, 2015;Francis et al, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, beliefs guide behaviour and behaviours affect beliefs interactively. Third, the data of Babayan et al (2018) concur with the finding that perceptual and memory-specific metacognitive representations coexist with generic confidence signals (Morales, Lau, & Fleming, 2018). In fact, activity in the anterior prefrontal cortex was reported to predict levels of confidence in a domain-specific fashion, whereas domaingeneral signals predicted confidence and accuracy in frontal and parietal midline areas.…”
supporting
confidence: 78%
“…In fact, since submission of this comment, it was shown in humans that neural encoding of meaningful information is related to dopamine release capacity in the striatum and reduced dopamine receptor availability in the midbrain (Nour et al, 2018). Furthermore, there are different brain networks for introspection and cognitive control (Morales et al, 2018). Also, the anterior insula has been shown to be involved in decisions to punish following the experience of harm, while activity in the amygdala was associated with the severity of punishment (Stallen et al, 2018).…”
mentioning
confidence: 99%